PREGNANCY RATES IN IN VITRO FERTILIZATION CYCLES AFTER THE TRANSFER OF EMBRYOS WITH MOSAIC KARYOTYPE IN PATIENTS WITH ADVANCED MATERNAL AGE - Feskov, O.M.; Zhylkova, Ye.S.; Blazhko, O.V.; Feskova, I.A.; Chumakova, N.O. (World of Medicine and Biology, 2025)
The technique of preimplantation genetic testing of embryos for aneuploidy makes it possible to select embryos with a balanced karyotype in case when assisted reproductive technologies are used. The literature provides data on the possibility of getting a normal pregnancy in patients when embryos with a low level of mosaicism of 20–40 % in the karyotype are transferred. The rates of blastocyst formation with balanced and mosaic karyotypes in women of different ages, and the clinical pregnancy rates after embryo transfer with mosaic karyotype in patients with advanced maternal age, were investigated in the present work. Increasing women's age was associated with decreased total blastocyst formation rate and the rate of blastocysts with high morphological quality (p=0.0044 and p=0.0190, respectively). Women aged 38 years or older are associated with an increased frequency of aneuploid embryo and blastocyst formation with a mosaic karyotype when using assisted reproductive technologies (p=0.00065 and p=0.0330, respectively). No statistically significant difference was found in clinical pregnancy rates between transferring embryos with a balanced karyotype and transferring blastocysts with a low level of mosaicism (p>0.05). A decrease in microscopic parameters of ejaculate leads to failures in the ability of sperm to fertilize a mature oocyte, even when the method of intracytoplasmic sperm injection was used when manipulating gametes in vitro (p=0.00504, p=0.000292, respectively).
Keywords: preimplantation genetic testing for aneuploidy; mosaicism; clinical pregnancy; assisted reproductive technologies